Analisis Penawaran Padi di Provinsi Bali - TRIYOKO, FARIST EDI; SUSRUSA, KETUT BUDI; ARTINI, NI WAYAN PUTU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2022)
Analysis of paddy Supply in Bali Province The agricultural sector, especially the food crops sub-sector, has an important rolein meeting the needs of carbohydrates and as a source of nutrition for sustainability human life. One of the main food crops consumed in Indonesia is paddy. Therefore, paddy should be a commodity that is of concern because it relates to the needs of many people. However, the Province of Bali has not yet become an area food self-sufficient because their paddy production from year to year actually suffers decline, thus affecting the supply of paddy. This research aims to analyze the factors that influence supply in the Province of Bali and to determine the level of sensitivity (elasticity) of paddy supply in Bali Province. Research method using quantitative data with secondary data sources time series (14 years). Data collection using recording techniques and also document review. Data analysis study used multiple linear regression analysis to determine the factors that affect the supply of paddy in the Province of Bali and the elasticity of the supply of paddy in the Province Bali. The results show the amount of production in the previous year, the harvested area in the previous year, the price of corn in the previous year, the price of soybeans inpreviously, the price of urea fertilizer in the previous year jointly affected on rice supply in Bali Province. While the amount of production in previously, individually significantly influenced paddy supply in Bali Province. The value of elasticity of paddy supply in Bali Province for the variable amount of paddy production inthe previous year, the harvested area in the previous year was inelastic, the price of corn in the previous year, the price of soybeans in the previous year, urea fertilizer in the year of planting is inelastic.